Sell-side debt analysts - Johnston, Rick; Markov, Stanimir; Ramnath, Sundaresh (Journal of Accounting and Economics, 2009)
We study the determinants and market impact of sell-side debt research. Analyzing a sample of 5920 debt reports published by 15 brokerage firms from 1999 to 2004, we document that companies with a higher probability of financial distress, lower market-to-book ratio, larger debt, and higher leverage receive more debt research. In addition, we document higher frequency of debt reports around credit ratings downgrades and find that their publication impacts equity prices. The evidence enhances our understanding of the nature of the market forces shaping sell-side debt research and its effect on price formation.